Application Of Thought-Stopping Therapy To Reduce Anxiety In Patients With Chronic Diseases At The University Of Indonesia Hospital - Ni Luh Emilia; Mustikasari ‎ (JOURNAL EDUCATIONAL OF NURSING(JEN), 2026)
Almost the entire world has serious problems with chronic diseases, where in addition to physical illness, patients also experience anxiety, so it is necessary to provide appropriate nursing care. The purpose of this case study is to provide nursing care by applying thought-stopping therapy to reduce anxiety in patients with chronic diseases. The study used a descriptive approach with 8 respondents. Data were obtained through interviews, observations, physical examinations, and measurement tools, which included signs and symptoms as well as anxiety levels. Thought-stopping therapy was conducted during the treatment process with 3 sessions and a schedule of 2 exercises per day in the morning and afternoon. The results showed a decrease in anxiety signs and symptoms with an average pre-treatment score of 50.38% and a post-treatment score of 4.92%, as well as an increase in patient ability from an average pre-treatment score of 12.12% to 46.97%. In conclusion, thought-stopping therapy can be used to reduce anxiety and improve the ability of patients with chronic diseases who experience anxiety. This therapy is recommended for use in nursing care for patients in hospitals. For other researchers, it is suggested to examine how long the effects of this therapy last and the need for trained caregivers to assist clients in performing this therapy at home.